O jogo de poderes institucionais no litígio territorial entre os municípios paraibanos de Serra Branca e Sumé: uma lógica às avessas - Souza, Suliman Sady de (2020)
This present work brings as the main discussion the dispute now verified between the municipalities of Serra Branca and Sumé, both located in the region of the Cariri Paraibano. The origin of this dispute lies in the decision of the IBGE to review the boundaries of these two municipalities in 2000, which would later be endorsed by the extinct INTERPA, a state body previously competent to ensure the administrative and judicial division of the State of Paraíba. In 2018, this territorial realignment was ratified by the ALPB, diametrically contradicting the will of the three rural communities that, ignored in this process, were affected and continue to suffer from the alteration of the boundary line that was in effect for more than a century. This change in limits impacted the receipt of constitutional funds in such a way that while the municipality of Serra Branca benefited, that of Sumé felt harmed. That is the main reason for the installation of this conflict. Differently from many other academic studies that deal with this theme approaching and guiding their debates strictly on what should be the real outline of the lines that separate one territory from another, this work seeks to emphasize institutional relations, or rather, power disputes and interests that orbit around this phenomenon and that may reflect a reality that needs to be better unraveled. The centrality of this study is, therefore, committed to analyzing the dispute concerning the Paraíba’s municipalities of Serra Branca and Sumé from the perspective of the territory as a propelling source of institutional power struggles and the contradictions contained therein. For this purpose, it seeks as a methodological path to be supported by an extensive bibliographic and documentary research, by field activities, occasions when interviews, photographic records, and survey of geographical coordinates were carried out. Methodologically, this research conforms in its entirety to the production of maps and the elaboration of graphs and tables that together subsidize the entire debate undertaken here. At first, a consistent theoretical foundation was chosen, in which the concepts of municipality and territory were revisited so that later it could support the discussion about how the process of forming the Cariri Paraibano took place. Based on this, three distinct phases of this “construction” of the Cariri space are identified. The first one was based on the “flag – corral – chapel (or farm) – camp” pattern, the second, according to our perception, was structured on the railroad – district – coronels rules – cotton pattern, while the third and current is represented by the highway – municipality – symbolic capital – goat-breeding pattern, as proposed in this work. The view on these different patterns, combined with the discussion concerning power, made it possible to identify in a next step in which context Serra Branca and Sumé arose and how the dispute that nowadays opposes these two municipalities emerged. This struggle gives rise, in addition to itself, to a competition of interests that are not limited only to the municipalities in question, which is what we seek to shed light upon in the final sequence of this research. In this work, other institutional subjects, especially those of a technical nature, are evidenced by the importance they exert in decisions that affect the populations of the territories in dispute. In the case of Serra Branca and Sumé, there is a dissonance of direction with the will of a population affected by a mandatory deterritorialization and a consequent compulsory jurisdictional reterritorialization.